An ultrasensitive NO2 gas sensor based on a hierarchical Cu2O/CuO mesocrystal nanoflower. Issue 35 (23rd August 2018) - Hu, Jing; Zou, Cheng; Su, Yanjie; Li, Ming; Han, Yutong; Kong, Eric Siu-Wai; Yang, Zhi; Zhang, Yafei
Abstract : A room temperature NO2 gas sensor with superior sensitivity and selectivity based on hierarchical Cu2 O/CuO mesocrystals. Abstract : Hierarchical Cu2 O/CuO mesocrystals have been fabricated by a one-step, controllable and low-power method. A novel "Etch-Oriented Self-Assembly" growth mechanism is proposed to describe the formation of hierarchical Cu2 O/CuO mesocrystals. In an alkaline environment, Cu2 O nanoparticles are generated first; they are then etched into small sized (14–18 nm) CuO nanocrystals which assemble in an oriented way to form Cu2 O/CuO mesocrystal nano-petals. As the reaction progresses, the obtained nano-petals stagger together to construct a hierarchical nanoflower structure. All factors that may influence the morphology of the final product have been investigated. The sensing results indicate that the product at 10 h exhibits the highest sensitivity to NO2 (73 162 to 10 ppm) at room temperature. Even when the concentration of NO2 drops down to 1 ppb, the sensing response of the Cu2 O/CuO-10 mesocrystals can reach 13.5. In addition, the sensor's response speed is ultra-fast and its response can increase to 2658 in 2 s when exposed to 10 ppm NO2 and recover 96% within 200 s. To study the sensor's response mechanism, the influence of pre-absorption of H2 O has been studied by experiments as well as the first-principles calculations, and a rational mechanism has been put forward to explain its distinctive sensing performance.